Fikih-Tasawuf dalam Pandangan Abdul Wahhab al-Sha'rani: Studi Analisis Akhd al-Hukmi Ikhtiyat Dalam Kitab Mizan Al-Kubra - Hadi, Misbahul Hadi; Ainul, Ainul Yaqin (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2022)
The Sufism teaches about search for meaning and the deepening of religion as a form of perfection by emphasizing the profound (esoteric) aspect rather than the outer (exoteric) through the system of wirid,riya>d{ah, muja>hadah and in such a way structured under the guidance of Spiritual guide (Mursyid). Thus, with the value of Sufism, the implementation of worship will be more perfect. This research becomes interesting when looking at the value of Sufism used as a lens or epistemology in taking Sharia law. This study seeks to discuss how Abdul Wahhab al-Sha'ra>ni's views on sufism and also taking of the law in an endeavor by considering the value of Sufism. The results of the study revealed that Abdul Wahhab al-Sha'ra>ni's views on sufism were synergistic. In his opinion, the aspects are interconnected and inseparable. It is proven in his work that he reveals various jurisprudence laws obtained using elements of Sufism with a kasyaf approach. However, the kasyaf t can be used has a special limitation, which must be based on sharia’s view. So that the results obtained are not contradictory. Meanwhile, Imam al-Sha'ra>ni's compromising form asserts that the ability to choose two aspects of the law, whether takhfi>f or tasydi>d, only applies when experiencing urgent circumstances. Because basically, the two aspects of takhfi>f or tasydi>d are tarti>b al-wujubi not takhyi>r. This kind of law-taking in the framework of prudence and to achieve the value of perfection in performing worship.